Implementation of Albert Bandura’s Social Learning Theory in Student Character Development - Khozin, Khozin; Tobroni, Tobroni; Rozza, Dian Silvia (International Journal of Advanced Multidisciplinary, 2024)
This research aims to describe and analyze teacher personality in shaping student character at school. This research uses a qualitative approach with a case study type in an elementary school. Data collection techniques were carried out using observation, interviews, and documentation. Data analysis techniques are carried out by condensing, presenting, and drawing conclusions. The research results show that teachers teachers have personality competencies and pedagogical competencies that encourage better learning. Teachers have attempted character development by integrating noble character values during school. This effort goes through four stages: attentional, retention, motor reproduction, and motivational. Suppose teachers can be good role models while at school, students will gradually be able to pay attention and become motivated by their actions. This will present student impulses that work below the level of consciousness to demonstrate the virtues modeled by the teacher. This is as explained in social learning theory by Albert Bandura.